ANALISIS, PERANCANGAN & IMPLEMENTASI APLIKASI E-COMMERCE BERBASIS WEB DI TOKO ABON ROJOKOYO - Muhammad Isroni; Donna Setiawati; Fariyono Fariyono (JITU : Journal Informatic Technology And Communication, 2019)
The title of this reseacrh is the analysis, design, and implementation of E-Commerce applications with web contents in the Abon Rojokoyo store to support marketing and promotion. With the application of E-Commerce can have a positive impact on the store, especially making it easier for consumers to shop anywhere and anytime. The method used in this study is the Waterfall method, which describes a systematic and sequential approach to software development.Starting with the analysis of the needs of the company or store, then proceeding through the stages of system design or design, coding/writing program code and finally the implementation / implementation of the program code. In making the website using the PHP (Hypertext Propocecos) programming language, the Apche server and the Mysql database that have been provided in the Xamp software. For the results achieved is an E-commerce web to support marketing and promotion systems and facilitate consumers in purchasing products.